Sosialisasi Pengadaan Tanah Untuk Proyek Pembangunan Jaringan Interkoneksi IPA Sepaku Semoi ke IPA Sepaku di Kabupaten Penajem Paser Utara - Indah Aulia Rizkika; Hariyadi Hariyadi; Hartana (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Land acquisition for strategic infrastructure is conducted through the release of land rights with fair compensation in accordance with Law Number 2 of 2012. The Interconnection Pipeline Network Project of IPA Sepaku Semoi to IPA Sepaku encountered land acquisition challenges that delayed construction progress. The method employed systematic coordination of administrative and technical verification involving LMAN, BPN, and OIKN. Based on direct observation during the internship period from 8 January to 28 February 2026, the results indicate that although 7,040 meters of pipeline route were ready in December 2025, the length increased to 8,214 meters by February 2026 following document verification and compensation payments. Through intensive socialization and a dialogic approach, community acceptance improved significantly. This ensured smooth land release, a reliable clean water supply for local residents, and positive economic contributions to the Ibu Kota Nusantara development area.